The Influence of English Ability on the Performance of the Secretary Director at Nunukan State Polytechnic - Harianti; Asrifan, Andi; Siti Hajar; Hasan Suksin (MultiTech Publisher, 2023)
This research aims to find out how English language skills influence the performance of the Secretary of the Director of the Nunukan State Polytechnic. The method used in this research is the questionnaire method, with primary data collection techniques through questionnaires and secondary data collection through library research. The data analysis used is a correlation technique to prove the influence of variable X or English language skills on the performance of the Secretary of the Director of the Nunukan State Polytechnic. Based on the results of the correlation test, it shows that there is an influence of English language skills on the performance of the Secretary of the Director of the Nunukan State Polytechnic, which has a positive but not significant effect. Thus, the initial hypothesis which states that there is no significant influence between English language skills on the performance of the Secretary and Director of the Nunukan State Polytechnic can be accepted. This is based on the results of tcount which is smaller than ttable (-1.347 < 1.701).